2015
DOI: 10.1007/s11051-015-2993-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticle-coated films: fabrication, characterization, and antibacterial properties

Abstract: ABSTRACT:In this article, novel antibacterial PVC-based films coated with ZnO nanoparticles (NPs) were fabricated, characterized and studied for their antibacterial properties. It exhibited more potent antibacterial activity than larger particles (1000 nm). All ZnOcoated films maintained antibacterial activity after 30 days in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For instance, among the six Gram-negative bacteria tested, only S. sonnei showed the largest inhibition zone of about 11.3 ± 0.6 mm with ZnO nanoparticles measuring 148 nm in size (milled for 2 h) comparable with the results shown by erythromycin, used as a positive control. A similar inhibition in Gram-negative bacteria was previously obtained for ZNPs of average particle sizes ranging 600-30 nm [9], 90-200 nm [40], 80 nm [13], 12-212 nm [8], 130-50 nm [57], and 5-38 nm [7]. Nevertheless, since the synthesis process of ZNPs difers in these studies, slight diferences in the inhibition activity should be mentioned.…”
Section: Microorganism-znp Interaction Mechanismssupporting
confidence: 83%
“…For instance, among the six Gram-negative bacteria tested, only S. sonnei showed the largest inhibition zone of about 11.3 ± 0.6 mm with ZnO nanoparticles measuring 148 nm in size (milled for 2 h) comparable with the results shown by erythromycin, used as a positive control. A similar inhibition in Gram-negative bacteria was previously obtained for ZNPs of average particle sizes ranging 600-30 nm [9], 90-200 nm [40], 80 nm [13], 12-212 nm [8], 130-50 nm [57], and 5-38 nm [7]. Nevertheless, since the synthesis process of ZNPs difers in these studies, slight diferences in the inhibition activity should be mentioned.…”
Section: Microorganism-znp Interaction Mechanismssupporting
confidence: 83%
“…In this regard, Li et al () showed that S. aureus growth was affected significantly by ZnO‐nanocomposite films. In another study (Jiang, O'Neill, & Ding, ), active films coated with ZnO NPs exhibited antibacterial activity against both gram‐positive ( S. aureus ) and gram‐negative ( E. coli ) bacteria. Similarly, Shankar et al () showed that gelatin‐ZnO NPs films have profound antimicrobial activity against both gram‐positive ( L. monocytogenes ) and gram‐negative ( E. coli ) bacteria.…”
Section: Discussionmentioning
confidence: 97%
“…Added the bacterial suspension 10 μL inoculated onto the entire surface of an agar. Each film sample was placed on the TSA surface [29]. The Petri dishes were incubated at 37 °C for 24 h and the clear zone were measured to determine the antibacterial activity.…”
Section: Methodsmentioning
confidence: 99%